The Comparison of EPS Standards and Analysis of the Usefulness of Basic and Diluted EPS - SOEGIHARTO SOEGIHARTO (The Indonesian Journal of Accounting Research, 2013)
This paper examines whether both basic earnings per share (BEPS) and diluted earnings per share (DEPS) have the potential to provide financial statement users with information that is useful for improving their decision making. It also explores the potential for BEPS and DEPS to function as useful input information in predictive decision models or in ranking‑decision models. This research is based on a study undertaken by DeBerg and Murdoch (1994) that examines the usefulness of EPS disclosure. The methodology of this research is modeled out based on theirs to test the same objects in an Australian setting. In addition, this study examines the effects of disclosure of both variations of EPS have on the market capitalization of firms. This study utilises the disclosures of listed firms in ASX over a four-year period. The results indicate that BEPS and DEPS contain essentially the same information and that disclosing both is superfluous. Since BEPS and DEPS, as well as price‑earnings (P/E) ratios computed using BEPS and DEPS are very highly correlated, it is quite improbable these data could be utilized as separate independent variables in a predictive decision model. Furthermore, ranking firms by price per basic earnings ratio (P/BE) and price per diluted earnings ratio (P/DE) results only in insignificant reordering.